Discrepant Effects of Oceanic Advection in the Evolution of SST Anomalies in the South China Sea During El Niño of Different Intensities - Xiao, Fuan; Wang, Dongxiao; Wu, Qiaoyan; Song, Wei; Zeng, Lili; Xie, Qiang; Wang, Yan (Frontiers in Marine Science, 2022)
Observed different evolutions of SST anomalies in the South China Sea (SCS) between super and other El Niño events are revealed. The results suggest that the first (second) warming peak is warmer than the second (first) one for super (other) El Niño composite. Mixed layer heat budget analysis indicates that during the first warming period, the vertical advection induced by the anomalous anticyclone in the SCS (SCSAC) warms the SST in the central SCS through the basin-scale downwelling motion for super El Niño composite. In contrast, the positive shortwave radiation anomalies from atmosphere into ocean associated with the reduced total cloud cover contribute the most warming SST for other El Niño composite. During the cooling period, the horizontal linear cold advection associated with a large west-east SST gradient anomaly and climatological western boundary currents plays the most important role in rapid cooling SST for super El Niño composite. However, the nonlinear warm advection associated with the northward current anomalies and anomalous SST gradient in the western SCS maintains the SCS SST for other El Niño composite. During the second warming period, the net surface heat flux anomalies act as a damping process, while the warming process could be attributed to the vertical warm advection. Specially, the SCSAC weakens but the anomalous easterly winds strengthen to suppress the upwelling off the coast of southeast Vietnam for other El Niño composite. The anomalous ocean circulations and associated advections are related to the development of SCSAC, which could be largely attributed to the SST anomalies in the Indian Ocean. In contrast with previous studies, our results highlight the role of ocean dynamics in the evolution of SCS SST anomalies during El Niño of different intensities.